'Soft, Wild and Free': A magical realist fairytale. (1st June 2021) - Liangi, Ifigeneia
'Soft, Wild and Free' is a magical realist fairytale about a creature that was soft and wild. It is also a magical realist fairytale about the courage of a guerilla princess who freed this creature from its foundations. With my research on magical realism, fairytales and the combination of the two, I am looking into fictional narratives that have the potential for the creation of spaces which are magical and critical. These fictional narratives exist in words and images that are constructed with a sensitivity to ideas of place and a place's spirit and character. Through the writing I bring together elements from magical realist literature and the classic magical fairytale, into a hybrid style, which then translates into drawings that I make physically and digitally. Clay, wood, card models, as well as sketches, orthographic drawings and paintings of buildings weave into a series of drawings whose scope is to suggest a version of architecture with a critical and poetic stance to the world. These drawings propose buildings as characters and characters as places that talk about the past and the present while imagining a poetic and critical future. In my work there are three types of processes, which are based on translations; two intersemiotic and one interlingual. The two intersemiotic translations are from writing to drawings and models and from drawings to writing; the interlingual translation is from modern Greek to English. These processes become spatial acts, as they allow for a perpetual generation of fictional and factual stories in words and images. My research is rooted in an inherent understanding of architecture through a literature that is critical and magical, an existential potion for our allegedly normal and normative world, which is really a wondrous, magical realist dream.